(untitled) (Journal of the College of Basic Education, 2023)
Colors and color schemes are considered one of the important studies in terms of the use of arts. Fine arts, mainly drawing and sculpting in the construction and design of theatrical show scenography elements represented by scenery, lighting, fashion, accessories and make-up, and in view of this importance, our study came In order to theoretically understand the issue of color schemes and the properties and connotations that they achieve, the study included The first chapter is the methodological framework in which the researcher deals with the research problem, the need for it, and the importance of it. The research, its objectives, and the limits of the research, then define the terms used, which are (employment,